O conceito constitucional de faturamento para efeitos de incidência da contribuição social ao PIS e a COFINS - Leal, Víctor Coutinho (2017)
This paper aims to determine the concept of the term "billing", provided for in the Constitution as the hypothesis of incidence for social contribution to the Social Integration Program (PIS) and Social Contribution for Social Security Financing (COFINS). Initially, it will analyze the legal system and its characteristics, in particular the constitutional tax system and the norms attributive to tax jurisdiction. It will show, in turn, that the concepts used to determine which materialities may affect social contributions consist of constitutional concepts, having a delimited and determined content. It will also be exposed the Karl Larenz interpretive method that will be used to determine the content of the legal-linguistic sign "billing". The study will also analyze the Social Rights and the evolution of social contributions in the Brazilian Constitutions, will relate the recognition of these as rights of immediate applicability and the institution of social contributions as tributes by the Political Charter of 1988. The work will evaluate the meaning of the term "billing", will seek its definition in other branches of Law, and will explain the incorporation by the Constitution of a specific concept of "billing". Finally, it will criticize the attempts to extend this concept by infraconstitutional norms and jurisprudence and will demonstrate the impossibility of this modification